'Bonbibi' Could Wait Till Our Boss Decides: Looking at the Changing Face of the Indian Sundarbans. (July 2021) - Mukhopadhyay, Prama
Internal migration constitutes a major source of steady flow of population in India, and reports published by the World Economic Forum (WEF), 1 2017 state that interstate migration in the country has doubled during 2001–2011, compared to the previous decade. 2 In developing countries, such migration is often considered to be an effective way for income diversification for the economically marginalised sections of the society, even though its effect on 'human development' is oft debated. This article would engage with this debate and bring out how migration from the Indian part of the Sundarbans to other parts of the country is not only changing the demography of the region but is also having a strong impact on the local perception and attachment towards the deltaic landscape. By bringing in ethnographic details from a village in the Indian Sundarbans, which was predominately inhabited by the fishing community earlier, this article would bring out how traditional occupations like fishing are slowly losing their popularity in the face of the lure of out-migration, as the very identity of the 'indigenous' Sundarban fisher folks—who were once rightfully considered to be the true conservator of the forests—is changing. From there, this article would engage with the broader debate of rethinking whether migration can be considered as a positive indicator of development in such ecologically fragile areas like the Sundarban deltas, which used to indeed have a distinct economic, social and cultural life of its own.